Social Justice in the Global South: the Cosmopolitanism Dimension of Indonesian Humanitarian Aid - Anabarja, Sarah; Farah Fadhilla, Nadya (Global Strategis, 2026)
In recent years, humanitarian aid has increasingly been executed including but not limited to social media activism, volunteering, and crowd-funding. Rather than being framed by the state or its agents, the discourse of social justice in delivering foreign aid has been reiterated along with solidarity as a driving force to help vulnerable target communities. Thus, we choose cases of humanitarian aid delivered to address the crises faced by the Rohingya and Palestinian peoples to represent the humanitarian crisis in the Global South. Through literature review and analysis of advocacy by civil society and government policy, this article finds that the activism of Indonesian Islamic NGOs is proven to be one of the determinant factors of Indonesian humanitarian aid in the Global South. The NGOs channel the voices and sentiments of their community toward their humanitarian aid activism. We develop the argument by examining the contributions of the prominent Islamic NGOs’ activism in mobilizing humanitarian aid as their interpretation of social justice norms in vulnerable societies in the Global South.  Keywords: Social Justice, Global South, Islamic NGOs, Cosmopolitanism, Indonesian Humanitarian aid.  Bantuan kemanusiaan adalah salah satu komponen penting dalam interaksi antar masyarakat internasional. Dalam perkembangannya, bentuk bantuan kemanusiaan semakin banyak dilangsungkan melalui beragam cara, termasuk ativisme sosial yang digerakkan oleh sukarelawan. Bergeser dari perspektif negara, ide terkait keadilan sosial dalam penyaluran bantuan kemanusiaan juga tercermin dari bentuk solidaritas yang ditujukan pada komunitas yang rentan secara transnasional. Artikel ini menilik kasus bantuan kemanusiaan yang dilakukan oleh masyarakat Indonesia bagi masyarakat Rohingya dan Palestina sebagai representasi krisis kemanusiaan di “Global South”. Melalui tinjauan literatur dan analisis pada aktivitas advokasi masyarakt sipil dan kebijakan pemerintah, artikel ini menemukan bahwa aktivisme Lembaga Swadaya Masyarakat (LSM) Islam di Indonesia terbukti menjadi salah satu faktor penentu bantuan kemanusiaan Indonesia. Penulis mengembangkan argumen ini dengan melihat kontribusi aktivisme LSM Islam terkemuka dalam memobilisasi bantuan kemanusiaan sebagai interpretasi mereka terhadap norma-norma keadilan sosial pada masyarakat rentan di “Global South”. Kata kunci: Keadilan Sosial, Global South, LSM Islam, Kosmopolitanisme, Bantuan Kemanusiaan Indonesia